KONFLIK SAMPANG: SEBUAH PENDEKATAN SOSIOLOGI-KOMUNIKASI - Handrini Ardiyanti (Sekretariat Jenderal DPR RI, 2012)
Social conflicts in Sampang, Madura, have often occurred between two different groups of Muslim, namely the Sunni and Shiite, who lives in the same region. This essay discusses the background of the social conflict and attempts to propose alternative conflict resolution. The writer argues the need to adopt a combination of sociology and communication approaches which tries to examine deeply the interaction between the two different Islam sects. Through such combination of approach, it is hoped therefore that the cases of the horizontal conflicts can be clearly explained and properly handled.